Effect of the 3-point line change on the game dynamics in girls' minibasketball - Arias, J. L.; Argudo, F. M.; Alonso, J. I. (Research Quarterly for Exercise and Sport, 2009)
We examined the game dynamics in minibasketball when comparing two different forms of the 3-point line. During the first competition, participants used a 3-point line delimited by the free-throw lane, and 1,642 ball possessions were recorded. During the second competition, participants played with a 3-point line delimited by a rectangular area, and 1,669 ball possessions were recorded. Results from the Mann-Whitney U Test show that when playing with a 3-point line delimited by the free-throw lane, higher average values were achieved in terms of points scored, number of players taking part in the ball possessions, number of passes, and one-on-one situations.